Therapeutic effect of mesenchymal stem cell-derived exosome therapy for periodontal regeneration: a systematic review and meta-analysis of preclinical trials - Liping Zhou; Wenjia Cai; Yuhan Zhang; Wenjie Zhong; Ping He; Jingsong Ren; Xiang Gao (Journal of Orthopaedic Surgery and Research)
Abstract Background To assess the therapeutic effects of mesenchymal stem cell (MSC)-derived exosome therapy on periodontal regeneration and identify treatment factors associated with enhanced periodontal regeneration in recent preclinical studies. Methods Searches were conducted in PubMed, Cochrane Library, EMBASE, and Web of Science databases until October 10, 2024. A risk of bias (ROB) assessment was performed using the SYRCLE tool. Osteogenic-related parameters were used as the primary outcome measures. Results In total, 1360 articles were identified, of which 17 preclinical studies were based on MSC-derived exosome therapy, and they demonstrated a beneficial effect on BV/TV (SMD = 13.99; 95% Cl = 10.50, 17.48; p < 0.00001), CEJ-ABC (SMD = -0.22; 95% Cl = -0.31, -0.13; p < 0.00001), BMD (SMD = 0.29; 95% Cl = 0.14, 0.45; p = 0.0002), and Tp.Sp (SMD = -0.08; 95% Cl= -0.15, -0.02; p = 0.02) compared with the control group. However, no significant differences were observed in Tp.Th (SMD = 0.03; 95% CI = 0.00, 0.07; p = 0.09) between the exosome-treated group and control group. Additionally, subgroup analysis indicated that preconditioned exosomes (p = 0.03) significantly improved BV/TV. In contrast, there were no significant differences in the enhancement of BV/TV with respect to the application method (p = 0.29), application frequency (p = 0.10), treatment duration (p = 0.15), or source of MSCs (p = 0.31). Conclusions MSC-derived exosomes show great promise for enhancing the quality of periodontal regeneration. However, more standardized and robust trials are needed to reduce heterogeneity and bias across studies and to confirm the therapeutic parameters associated with the enhancement of periodontal regeneration by MSC-derived exosomes. Registration CRD42024546236.